ChemInform Abstract: In Situ Analysis of Catalytically Active Pd Surfaces for CO Oxidation with Near Ambient Pressure XPS. Issue 4 (January 2016) - Kondoh, Hiroshi; Toyoshima, Ryo; Monya, Yuji; Yoshida, Masaaki; Mase, Kazuhiko; Amemiya, Kenta; Mun, Bongjin Simon
Abstract: Review: 45 refs.